Consider the operation is
.
Given:
The augmented matrix below represents a system of equations.
![\left[\left.\begin{matrix}1&0&1\\1&3&-1\\3&2&0\end{matrix}\right|\begin{matrix}-1\\-9\\-2\end{matrix}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cleft.%5Cbegin%7Bmatrix%7D1%260%261%5C%5C1%263%26-1%5C%5C3%262%260%5Cend%7Bmatrix%7D%5Cright%7C%5Cbegin%7Bmatrix%7D-1%5C%5C-9%5C%5C-2%5Cend%7Bmatrix%7D%5Cright%5D)
To find:
Matrix results from the operation
.
Step-by-step explanation:
We have,
![\left[\left.\begin{matrix}1&0&1\\1&3&-1\\3&2&0\end{matrix}\right|\begin{matrix}-1\\-9\\-2\end{matrix}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cleft.%5Cbegin%7Bmatrix%7D1%260%261%5C%5C1%263%26-1%5C%5C3%262%260%5Cend%7Bmatrix%7D%5Cright%7C%5Cbegin%7Bmatrix%7D-1%5C%5C-9%5C%5C-2%5Cend%7Bmatrix%7D%5Cright%5D)
After applying
, we get
![\left[\left.\begin{matrix}1&0&1\\-3(1)&-3(3)&-3(-1)\\3&2&0\end{matrix}\right|\begin{matrix}-1\\-3(-9)\\-2\end{matrix}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cleft.%5Cbegin%7Bmatrix%7D1%260%261%5C%5C-3%281%29%26-3%283%29%26-3%28-1%29%5C%5C3%262%260%5Cend%7Bmatrix%7D%5Cright%7C%5Cbegin%7Bmatrix%7D-1%5C%5C-3%28-9%29%5C%5C-2%5Cend%7Bmatrix%7D%5Cright%5D)
![\left[\left.\begin{matrix}1&0&1\\-3&-9&3\\3&2&0\end{matrix}\right|\begin{matrix}-1\\27\\-2\end{matrix}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cleft.%5Cbegin%7Bmatrix%7D1%260%261%5C%5C-3%26-9%263%5C%5C3%262%260%5Cend%7Bmatrix%7D%5Cright%7C%5Cbegin%7Bmatrix%7D-1%5C%5C27%5C%5C-2%5Cend%7Bmatrix%7D%5Cright%5D)
Therefore, the correct option is A.
f(x)=x3−5
Replace f(x)
with y
.
y=x3−5
Interchange the variables.
x=y3−5
Solve for y
.
Since y
is on the right side of the equation, switch the sides so it is on the left side of the equation.
y3−5=x
Add 5
to both sides of the equation.
y3=5+x
Take the cube root of both sides of the equation to eliminate the exponent on the left side.
y=3√5+x
Solve for y
and replace with f−1(x)
.
Replace the y
with f−1(x)
to show the final answer.
f−1(x)=3√5+x
Set up the composite result function.
f(g(x))
Evaluate f(g(x))
by substituting in the value of g into f
.
(3√5+x)3−5
Simplify each term.
Remove parentheses around 3√5+x
.
f(3√5+x)=3√5+x3−5
Rewrite 3√5+x3
as 5+x
.
f(3√5+x)=5+x−5
Simplify by subtracting numbers.
.
Subtract 5
from 5
.
f(3√5+x)=x+0
Add x
and 0
.
f(3√5+x)=x
Since f(g(x))=x
, f−1(x)=3√5+x is the inverse of f(x)=x3−5
.
f−1(x)=3√5+x
Answer:
The answer to your question is: ( x + 6 ) ( x - 2 )
Step-by-step explanation:
Factor x² + 4x - 12 = 0
Find two numbers that added gives +4 and if we multiply them get -12
We can find these numbers by decomposing -12 in its prime factors
12 2
6 2 12 = 2 x 2 x 3
3 3 now combine the numbers to get -12 and + 4
1 2 and 2 x 3 = 6
and 2 x 6 = 12
Then
( x + 6 ) ( x - 2 )
Answer:
ummmm
Step-by-step explanation:
why?
2,050,000 = 40,000 * a
a = 2,050,000 / 40,000 = 51.25 m/s^2